A Unique Subset: Idiopathic Intracranial Hypertension Presenting as Spontaneous CSF Leak of the Anterior Skull Base - Hong, Christopher S.; Kundishora, Adam J.; Elsamadicy, Aladine A.; Vining, Eugenia M.; Manes, R. Peter; Omay, Sacit Bulent (Journal of Neurological Surgery Part B: Skull Base, 2021)
Introduction Spontaneous cerebrospinal fluid (CSF) leaks represent a unique clinical presentation of idiopathic intracranial hypertension (IIH), lacking classical features of IIH, including severe headaches, papilledema, and markedly elevated opening pressures.Methods Following a single-institution retrospective review of patients undergoing spontaneous CSF leak repair, we performed a literature review of spontaneous CSF leak in patients previously undiagnosed with IIH, querying PubMed.Results Our literature review yielded 26 studies, comprising 716 patients. Average age was 51 years with 80.8% female predominance, and average body mass index was 35.5. Presenting symptoms included headaches (32.5%), visual disturbances (4.2%), and a history of meningitis (15.3%). Papilledema occurred in 14.1%. An empty sella was present in 77.7%. Slit ventricles and venous sinus stenosis comprised 7.7 and 31.8%, respectively. CSF leak most commonly originated from the sphenoid sinus (41.1%), cribriform plate (25.4%), and ethmoid skull base (20.4%). Preoperative opening pressures were normal at 22.4 cm H2O and elevated postoperatively to 30.8 cm H2O. 19.1% of patients underwent shunt placement. CSF leak recurred after repair in 10.5% of patients, 78.6% involving the initial site. A total of 85.7% of these patients were managed with repeat surgical intervention, and 23.2% underwent a shunting procedure.Conclusion Spontaneous CSF leaks represent a distinct variant of IIH, distinguished by decreased prevalence of headaches, lack of visual deficits, and normal opening pressures. Delayed measurement of opening pressure after leak repair may be helpful to diagnose IIH. Permanent CSF diversion may be indicated in patients exhibiting significantly elevated opening pressures postoperatively, refractory symptoms of IIH, or recurrent CSF leak.
Keywords: CSF leak; anterior skull base; intracranial hypertension; pseudotumor